The bears' famous invasion of Sicily - Buzzati, Dino, 1906-1972.; Lobb, Frances; Snicket, Lemony (New York : HarperTrophy, 2005)
In search of food, Leander, King of the Bears, leads his subjects from their safe caves in the mountains of Sicily to the valley where they triumph over many enemies.
translated from the Italian by Frances Lobb ; introduction and reader's companion by Lemony Snicket.
Originally published: New york Review of Books, 2003.
Keywords: Fairy tales; Bears -- Fiction; Kings, queens, rulers, etc. -- Fiction; Sicily (Italy) -- Fiction; Italy -- Fiction